Pelatihan Instalasi Jaringan Dan Hotspot Menggunakan Mikrotik Bagi Siswa SMKs NWDI Wanasaba - Permana, Baiq Andriska Candra; Indra Gunawan; Muhammad Wasil; Harianto; Aris Sudianto; Mahpuz; Jumawal; Muhamad Sadali; Suhartini; Lalu Kertawijaya; Ida Wahidah; Muhammad Djamaluddin; Imam Fathurrahman; Hamzan Ahmadi (Universitas Hamzanwadi, 2024)
With the development of industrial technology, this requires students to continue to adapt to keep up with technological developments. The increasing use of internet technology is not only popular among students but also in various agencies in the world of work. At a basic level, understanding network installation and configuration is one of the competencies taught in the Informatics and networking department at Vocational High Schools (SMK). The existence of network technology causes many conveniences including students being able to share resources such as scanners, printers, hard disks and others by simply connecting to the network. There are so many benefits that will be obtained by students by mastering skills in the field of network technology. This is one of the reasons for conducting training to improve student competence in the field of network installation and configuration. The method applied in this training activity is Participatory Learning and Action (PLA) where this method is an approach used in community development that focuses on the active participation of the community in the learning and decision-making process. The results of this activity are expected to have a positive impact on the competence of students at SMKs NWDI Wanasaba in the field of computer network technology so as to increase student confidence in facing school competency exams.